2012
DOI: 10.1002/pmic.201100573
|View full text |Cite
|
Sign up to set email alerts
|

Close proximity of phosphorylation sites to ligand in the phosphoproteome of the extreme thermophile Thermus thermophilusHB8

Abstract: We performed phosphoproteome analysis of proteins from the extremely thermophilic Gram-negative eubacterium Thermus thermophilus HB8 using gel-free mass spectrometric method. We identified 52 phosphopeptides from 48 proteins and determined 46 phosphorylation sites: 30 on serine, 12 on threonine, and 4 on tyrosine. The identified phosphoproteins are known to be involved in a wide variety of cellular processes. To help elucidate the functional roles of these phosphorylation events, we mapped the phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 74 publications
2
24
0
Order By: Relevance
“…Among the identified phosphopeptides, the locations of 67 nonredundant phosphorylation sites were determined with the highest level of confidence (class I sites: 99% peptide identification confidence (48)): 38 (56.7%) on serine, 24 (35.8%) on threonine, and 5 (7.4%) on tyrosine. The relative Ser/Thr/Tyr phosphorylation ratio was similar to that of other bacterial phosphoproteomes (28,29,31,33,35). Annotated MS/MS spectra of all identified phosphopeptides and a detailed list of the identified phosphoproteins are provided in supplemental Fig.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Among the identified phosphopeptides, the locations of 67 nonredundant phosphorylation sites were determined with the highest level of confidence (class I sites: 99% peptide identification confidence (48)): 38 (56.7%) on serine, 24 (35.8%) on threonine, and 5 (7.4%) on tyrosine. The relative Ser/Thr/Tyr phosphorylation ratio was similar to that of other bacterial phosphoproteomes (28,29,31,33,35). Annotated MS/MS spectra of all identified phosphopeptides and a detailed list of the identified phosphoproteins are provided in supplemental Fig.…”
Section: Resultssupporting
confidence: 56%
“…In a comparison of phosphoproteomes within the same species (i.e. T. thermophilus strains HB27 (this study) and HB8 (35)), ϳ45% of the phosphoproteins were found to be identical (supplemental Table S8), and, with the exception of valyl-tRNA synthetase (TTC0805) and chaperonin GroEL (TTC1714), the phosphorylation sites of these proteins were the same. The remaining 55% of the phosphoproteins of these two closely related thermophiles were distinct, perhaps accounting for strain-specific differences in regulatory mechanisms and biological functions.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Recently, we reported the results of phosphoproteome and acetylome analyses performed during a proteomic characterization of Thermus thermophilus HB8, an extremely thermophilic Gram-negative eubacterium (22,33). The 2.2-Mb genome of T. thermophilus HB8 contains 2238 open reading frames, about half the number in Escherichia coli.…”
mentioning
confidence: 99%
“…The simplicity of this genome is greatly advantageous in attempts to achieve a comprehensive understanding of the bacterium's physiology. We have studied T. thermophilus as a model organism with the goal of understanding biological phenomena in bacteria, using "-omics" approaches such as structural genomics (34 -36), transcriptomics (37), metabolomics (38), whole-cell proteomics (39), and PTM proteomics (22,33).…”
mentioning
confidence: 99%